2002
DOI: 10.1103/physrevlett.89.206805
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Structure of the Electron Spin Resonance of Phosphorus-Doped Si Nanocrystals

Abstract: Electronic states of P donors in Si nanocrystals (nc-Si) embedded in insulating glass matrices have been studied by electron spin resonance. Doping of P donors into nc-Si was demonstrated by the observation of optical absorption in the infrared region due to intraconduction band transitions. P hyperfine structure (hfs) was successfully observed at low temperatures. The observed splitting of the hfs was found to be much larger than that of the bulk Si:P and depended strongly on the size of nc-Si. The observed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
160
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 14 publications
14
160
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] In particular, it has been shown that electrically-activated impurity atoms located in substitutional sites tend to enhance the conductivity. [6][7][8][9][10] Theoretically, several works have studied the formation and ionization energies, and the opto-electronic properties of freestanding doped SiQDs.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] In particular, it has been shown that electrically-activated impurity atoms located in substitutional sites tend to enhance the conductivity. [6][7][8][9][10] Theoretically, several works have studied the formation and ionization energies, and the opto-electronic properties of freestanding doped SiQDs.…”
Section: Introductionmentioning
confidence: 99%
“…The donor level in SiNCs has been known to be a little bit deeper ͑ϳ60 meV͒ than that ͑ϳ40 meV͒ of bulk crystal Si from larger ESR splitting of the hyperfine structure of P donors in SiNCs. 3,4 Since the numbers of Si atoms contained in each SiNC with diameters of 3 and 5 nm are estimated to be approximately 680 and 3100, the number of allowed levels near the bottom of the discrete conduction band of each SiNC is much smaller compared to the states near the bottom of the continuum conduction band of bulk Si. Consequently a fraction of donor electrons is still bound by donor levels in SiNCs even at RT, which is entirely different from donors in bulk Si.…”
Section: -3mentioning
confidence: 99%
“…Fujii and co-workers 3,7 reported P doping effects for PL intensity that light doping produces enhancement of PL for SiNCs with relatively small sizes, but not for those for larger SiNCs, and heavy P doping leads to decrease in PL intensity. The latter is due to Auger nonradiative recombination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations